Tracing the Roots of American Cinematic Vilification of Arabs and Muslims - MECHERI , Fatima Zohra (Journal of Human Sciences, 2023)
American cinema is imbued with stereotypical representations of various ethnic and racial groups, but of the many stereotypes and misrepresentations that plague Hollywood those of the Muslim world and its inhabitants have ostensibly been the most damaging and resilient. Ever since the camera began to crank, Hollywood has propagated Arabs and Muslims in exotic terms. The Arab/Muslim appears as an unkempt, uncivilized, and violent terrorist character in over thousand movies. This article analyzes what promotes the ubiquitous negative image of Arabs and Muslims, where it comes from, and why it persists in American cinema and attempts to show how the American cultural fear of the ‘Other’ (the Other being that who challenges the United States national ideology) has resulted in the creation of the dangerous ‘Arab Other’ in American motion picture industry.